Investigation into the influence of magnesia content, alumina content, basicity and ignition temperature on the mineralogy and properties of iron sinter - Garbers-Craig, Andrie Mariana (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.